Superalloys 1996 (Eighth International Symposium) 1996
DOI: 10.7449/1996/superalloys_1996_687_695
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Path Dependant Behavior of a Supersolvus Heat Treated Nickel Base Superalloy

Abstract: A key business initiative for jet engine manufactures is to reduce the engine development cycle time, Cycle time reductions lead to reduced introduction costs, and allow the manufacturer to get their product to market before their competitors. Two materials evaluation techniques are presented that allow for significant reductions in cost and time during the development of new turbine components. The on-cooling tensile test produces data that, when coupled with thermal/stress models, allows for the design of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…It was also discovered that crack growth rates decrease with an increase in γ ′ size in both the bulk and the skin microstructures of alloy N18; 78 assuming Ostwald ripening occurs, an increase in γ ′ size implies larger channels between the precipitates for dislocation movement and again plastic strain is accommodated more easily. This finding was also corroborated by Kissinger 86 who performed different cooling treatments from the solutionising temperature in Rene 88DT to achieve different γ ′ size distributions and spacing. Some of these same concepts may also be applied to optimising γ ′ volume fractions and size distributions to mitigate crack nucleation due to slip band cracking.…”
Section: Long Crack Growth Mechanisms and Models In Nife-based Supera...supporting
confidence: 66%
“…It was also discovered that crack growth rates decrease with an increase in γ ′ size in both the bulk and the skin microstructures of alloy N18; 78 assuming Ostwald ripening occurs, an increase in γ ′ size implies larger channels between the precipitates for dislocation movement and again plastic strain is accommodated more easily. This finding was also corroborated by Kissinger 86 who performed different cooling treatments from the solutionising temperature in Rene 88DT to achieve different γ ′ size distributions and spacing. Some of these same concepts may also be applied to optimising γ ′ volume fractions and size distributions to mitigate crack nucleation due to slip band cracking.…”
Section: Long Crack Growth Mechanisms and Models In Nife-based Supera...supporting
confidence: 66%
“…Studies have been conducted to study quench crack sensitivity of Rene'95, R'88DT, and U720LI as a function of temperature, and cooling rate from solution heat treatment. [13,48,49] It has been shown that the inherent toughness of R'95 is one order of magnitude lower at solution temperatures than at room temperature. [13] Quench cracking occurs by complete intergranular failure.…”
Section: Heat Treatment Processing Of Nickel-base Superalloysmentioning
confidence: 99%
“…It is thought that quench cracking can be modeled and predicted by either: fracture mechanics methods, [13,50] using the material's K 1C or K Q properties; or simply by a tensile stress overload criterion using the material's ultimate tensile strength properties. [48] Although the fracture mechanics method seems the most appropriate approach, the tensile overload method is the easiest and is the most prevalently used.…”
Section: Heat Treatment Processing Of Nickel-base Superalloysmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In the case of superalloys, such databases have been developed to include up to 13 elements and also a large number of phases of practical interest. 9…”
Section: Introductionmentioning
confidence: 99%